Linear extensions of dynamical systems on a torus that possess Green-Samoilenko functions - Wojtowicz, B.; Kulik, V. L.; Вуйтович, Б.; Кулик, В. Л.; Вуйтович, Б.; Кулик, В. Л. (Institute of Mathematics, NAS of Ukraine, 1998)
By using Lyapunov functions with alternating signs, we study problems of regularity and weak regularity for some linear extensions of dynamical systems on a torus.